2018
DOI: 10.3389/fphar.2018.00577
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Assay of hERG K+ Channel Potency for a New EGFR Inhibitor FHND004

Abstract: FHND004 is a newly synthesized epidermal growth factor receptor (EGFR) inhibitor for the treatment of non-small cell lung cancer (NSCLC). The aim of the present study was to investigate the impacts of FHND004 on human ether-à-go-go-related gene (hERG) K+ channels and the molecular mechanisms underlying of its action. Whole-cell patch clamp recording was performed on wild type (WT), mutant hERG channels heterologously expressed in human embryonic kidney (HEK) 293 cells or IKr endogenously expressed in HL-1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…In our study, lazertinib had an IC 50 of 5.3 μM in the hERG cellular patch-clamp assay, whereas an earlier study of osimertinib reported an IC 50 of 0.57 μM in a similar assay. 31 Our preclinical data thus support the idea that lazertinib might have reduced potential for HER2- or hERG-related cardiotoxicity, compared with other TKIs.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, lazertinib had an IC 50 of 5.3 μM in the hERG cellular patch-clamp assay, whereas an earlier study of osimertinib reported an IC 50 of 0.57 μM in a similar assay. 31 Our preclinical data thus support the idea that lazertinib might have reduced potential for HER2- or hERG-related cardiotoxicity, compared with other TKIs.…”
Section: Discussionsupporting
confidence: 76%
“…In our prior study of a minimally structured high affinity hERG inhibitor, Cavalli-2, mutation at F656 had greater effects on blocking potency than mutation at either F557 or Y652 [27]. An independent study of a novel EGFR inhibitor FHND004 also found mutation at F656 to attenuate inhibition more than at F557 [48]. Sarizotan is notable in this regard as it is an I hERG inhibitor for which mutation of F557 produces a greater attenuation of inhibition than mutation at the canonical F656 binding residue.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR are linked to many potassium channels, i.e., Kv1.3 ( 15 ), Kv10.1 ( 16 ), Kv4.3 ( 17 ), and Kir2.3 ( 18 ), which are modulated by EGFR kinase via phosphorylation of tyrosine in their specific residues. Osimertinib has been proved as a weak inhibitor of the cardiac potassium ion channel, Kv11.1, inhibiting hERG encoded potassium channel function with an in vitro IC50 of 0.69 mM ( 19 ). Spontaneous release of Ca 2 + via cardiac ryanodine receptors (RyR2), through a process termed store overload-induced Ca 2 + release (SOICR), is a common mechanism underlying arrhythmia.…”
Section: Discussionmentioning
confidence: 99%